Opportunities for sensing systems in mining - Kiziroglou,M; boyle,D; Yeatman,E; Cilliers,J (IEEE Transactions on Industrial Informatics, 2016)
Pervasive sensing - the capability to deploy large numbers of sensors, to link them to communication networks, and to analyze their collective data - is transforming many industries. In mining, networked sensors are already used for remote operation, automation including driverless vehicles, health and safety, and exploration. In this paper, the state-of-the-art sensing and monitoring technologies are assessed as solutions against the main challenges and opportunities in the mining industry. Localization, mapping, remote operation, maintenance and health and safety are identified as the main beneficiaries, from rapidly developing technologies such as 3D visualization, augmented reality, energy autonomous sensor nodes, distributed sensing, smart network protocols and big data analytics. It is shown that the identification and management of ore grade in particular, which transcends each stage of the mining process, may critically benefit from certain arising sensing technologies, where major efficiency improvements are possible in exploration, extraction, haulage and processing activities.